2020
DOI: 10.1128/aac.00321-20
|View full text |Cite
|
Sign up to set email alerts
|

KPC-50 Confers Resistance to Ceftazidime-Avibactam Associated with Reduced Carbapenemase Activity

Abstract: KPC-50 is a KPC-3 variant identified from a Klebsiella pneumoniae clinical isolate recovered in Switzerland in 2019. Compared to KPC-3, KPC-50 shows (i) a three-amino-acid insertion (Glu-Ala-Val) between amino acids 276 and 277, (ii) an increased affinity to ceftazidime, (iii) a decreased sensitivity to avibactam, explaining the ceftazidime-avibactam resistance, and (iv) an association with a sharp reduction of its carbapenemase activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 22 publications
2
18
0
Order By: Relevance
“…Reduced MICs of AZT and IMI were observed against KP21 carrying the D178Y variant, compared with KP21 carrying wild-type KPC-3 (Table 2). This phenomenon of reduced spectrum of β-lactamase activity has been described for other bla KPC-3 mutants associated with CAZ/AVI resistance (3)(4)(5)(6).…”
Section: Textsupporting
confidence: 59%
See 1 more Smart Citation
“…Reduced MICs of AZT and IMI were observed against KP21 carrying the D178Y variant, compared with KP21 carrying wild-type KPC-3 (Table 2). This phenomenon of reduced spectrum of β-lactamase activity has been described for other bla KPC-3 mutants associated with CAZ/AVI resistance (3)(4)(5)(6).…”
Section: Textsupporting
confidence: 59%
“…Avibactam is currently in clinical use partnered by ceftazidime (CAZ/AVI) and here, mutations in KPC are known to confer resistance. However, such mutations tend to reduce hydrolytic activity to β-lactams other than ceftazidime, including carbapenems and aztreonam (3)(4)(5)(6). Accordingly, it is conceivable that such mutant KPC enzymes might not confer AZT/AVI resistance.…”
Section: Textmentioning
confidence: 99%
“…Likewise, a novel bla KPC-3 variant ( bla KPC-50 ) was recently identified in multi-drug resistant K . pneumoniae clinical isolate conferring resistance to ceftazidime-avibactam in Switzerland that was most likely acquired in Greece [ 58 ]. Several studies have demonstrated that medical tourism is another way to introduce CREs from an endemic country to a non-endemic country [ 59 , 60 , 61 ].…”
Section: Carbapenemases-producing Enterobacteriaceae mentioning
confidence: 99%
“…It has proven active against serine β-lactamases, including Klebsiella pneumoniae carbapenemases (KPC), which otherwise confer resistance to most β-lactams and β-lactam/β-lactamase inhibitor combinations (1). Despite limited clinical use worldwide, acquired resistance has been reported in multiple, independent occurrences and by several mechanisms in both patients with or without a history of CZA therapy (3)(4)(5)(6)(7)(8)(9)(10)(11) resolved after ~4 weeks of treatment with CZA (Fig. 1A).…”
Section: Main Textmentioning
confidence: 99%
“…Tazobactam and avibactam were added at a fixed concentration of 4 μg/ml 2. Performed in duplicate using a VITEK2 in the MRSN CAP-accredited laboratory 3. Performed in two biological duplicates (distinct transformants confirmed by Sanger sequencing) using a Gram Negative GN4F AST Plate (Thermo Fisher).nd, not determined.on May 23, 2021 by guest http://aac.asm.org/ Downloaded from…”
mentioning
confidence: 99%